2015
DOI: 10.1002/pssc.201400172
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of external quantum efficiency of AlGaN UV LEDs grown by hydride vapor phase epitaxy

Abstract: A comparative study of the degradation of HVPE‐grown 360 nm AlGaN/GaN UV and commercially available InGaN/GaN blue LED chips was performed. The common feature of the degradation of these two types of LEDs was found to be the increase of the conductivity of shunt paths under current injection. The paths (shunts) are localized in the extended defects system (EDS). It is proposed that the conductivity increase is due to defect formation under multiphonon carriers recombination in a part of the EDS enriched by Ga … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Degradation of blue GaN/InGaN MQW LEDs prepared by MOCVD and near-UV AlGaN/GaN DH LEDs grown by HVPE was studied by Shmidt et al [375]. The authors observed a somewhat similar behavior in both cases: an increase with aging of the forward current and reverse current attributed to enhanced tunneling via dislocations decorated by point defects.…”
Section: V2leds Degradation Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…Degradation of blue GaN/InGaN MQW LEDs prepared by MOCVD and near-UV AlGaN/GaN DH LEDs grown by HVPE was studied by Shmidt et al [375]. The authors observed a somewhat similar behavior in both cases: an increase with aging of the forward current and reverse current attributed to enhanced tunneling via dislocations decorated by point defects.…”
Section: V2leds Degradation Studiesmentioning
confidence: 91%
“…The formation of such shunts was ascribed to local heating of the structures causing In or Al segregation on dislocations [378]. The lifetime of the near-UV AlGaN/GaN DH LEDs was found to be considerably lower than for blue GaN/InGaN MQW LEDs, even though the dislocation density in the AlGaN/GaN structures was not higher [375].…”
Section: V2leds Degradation Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Keeping pace with research and investigation carried out thus far on the III-nitrides semiconductors, stemming from binary GaN to ternary Al x Ga 1-x N and In y Ga 1-y N [11][12][13][14][15][16][17], as well as quaternary Al x In y Ga 1-x-y N [18][19][20], significance of growing optimum III-nitrides heterostructures for quantum wells with regards to the LEDs performance is unveiled.…”
Section: Accepted Manuscript Intrmentioning
confidence: 97%
“…Этот параметр отражает степень нарушения локальной симметрии внутренних связей самоподобных фракталов в целое и используется в современном мате-риаловедении для характеризации материалов со слож-ной внутренней структурой. Для синих светодиодов, а также светодиодов на длину волны 368 нм, полученных из структур, классифицированных количественно по значению этого параметра, была выявлена корреляция уровня проводимости нелинейных шунтов и искажений прямой ветви ВАХ при малых смещениях, а также срока службы светодиодов с величиной этого парамет-ра [13,14]. Увеличение параметра p , как было показано в [7], сопровождается увеличением областей трехмер-ного роста, увеличением неоднородного распределения дислокаций в структуре, образованием скоплений дисло-каций, увеличением на порядки проводимости нелиней-ных шунтов.…”
Section: Introductionunclassified